Associations Between Temperature and Location of Injury or Condition Among Heat‐Related Emergency Department Visits - Chen Li; Hua Hao; Morgan Lane; Noah Scovronick; Rebecca Zhang; Stefanie Ebelt; Howard H. Chang (GeoHealth)
Abstract High ambient temperature poses significant health risk globally. However, the relative importance of different exposure pathways leading to health risks remains unclear. For 9 US states during 2016–2018, ED visit records for heat exhaustion and heat stroke (HEAT), fluid and electrolyte imbalance (FEI), volume depletion (VD), and acute kidney injury (AKI) were identified via diagnosis codes. Co‐diagnosed Y92 subcodes (Y codes) were used to categorize the patient's location at the time of injury or condition. Logistic regressions were used to estimate nonlinear associations between same‐day temperature and Y codes for 11 non‐residential versus residential locations among heat‐related ED visits, including stratified analyses by patient age, race, and ethnicity. Odds ratios (OR) were calculated between the 95th versus 50th percentile of temperature. Overall, higher temperature was associated with increased risks of ED visits with Y codes for non‐residential locations. HEAT ED visits were more likely to have Y codes for streets compared to residential locations (OR:1.68, 95% CI: 1.12–2.51). Similarly, VD visits were more likely to have Y codes for industrial area (OR: 2.68, 95% CI: 1.98–3.63), farms (OR:7.66, 95% CI: 4.05–14.50), recreation areas (OR:2.25, 95% CI: 1.78–2.84), and streets (OR:1.54, 95% CI: 1.39–1.70), but were less likely to have Y codes for public places (OR: 0.89, 95% CI: 0.84, 0.94). Similar associations were observed for FEI and AKI ED visits. Locations associated with higher heat risks may be due to exposure outdoor temperature and activities, supporting the need to develop strategies and interventions that minimize heat exposure in these areas.